Relevansi Penerapan Teori Hukum pada Hukum Kesehatan Terkait Hak dan Kewajiban Dokter dalam Melakukan Pelayanan Kesehatan - Annisa Dea; Abdul Rahman Maulana Siregar (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
In the word legal theory is a foundation, opinion, understanding related to reality by describing the hypotheses studied. Theory provides an explanatory understanding by organizing the problems being faced, the purpose of methodological deepening in the background in order to obtain better and broader knowledge to solve related issues. In the world of health, theory is very necessary before carrying out field practice that directly involves dealing directly with patients to provide good health services. The application of legal theory in the world of health provides an understanding in studying the law that is clearer about legal materials and systematic views on legal statements. In this case, it is also inseparable from legal theory in medical practice, because in providing health services, doctors in the profession know their rights and obligations.